2020
DOI: 10.1111/ipd.12734
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric maxillofacial fractures in Ghana: Pattern, household cost, and distress

Abstract: Background Maxillofacial fractures in the paediatric population are peculiar in risks, management, and potential complications. Aim To determine the pattern, psychological distress to parents, and economic cost of paediatric maxillofacial fractures in Ghana. Design This study combined a retrospective evaluation with a cross‐sectional cost‐of‐illness (COI) analysis to describe the pattern and economic cost of paediatric maxillofacial fractures in Ghana. The DASS 21 was used to assess psychological distress to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The adolescent age group (13 -17 years) reported the most soft tissue injuries 64 (42.4%). This result was also similar to the study done at the Korle-bu Teaching Hospital in Accra by Blankson et al [21] which showed that adolescent-aged children within 13 -17 sustained the most injuries, followed by the School-aged children.…”
Section: Discussionsupporting
confidence: 91%
“…The adolescent age group (13 -17 years) reported the most soft tissue injuries 64 (42.4%). This result was also similar to the study done at the Korle-bu Teaching Hospital in Accra by Blankson et al [21] which showed that adolescent-aged children within 13 -17 sustained the most injuries, followed by the School-aged children.…”
Section: Discussionsupporting
confidence: 91%
“…For the three studies (1%) that used the willingness to pay approach, the patient or caregiver provided the maximum daily amount of money that they would be willing to pay to hire a substitute worker to replace the sick household member [ 43 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of 58 studies 7,9,11,21–75 included in the meta‐analysis are shown in Table 1. The studies included a case range of 37–183,336 cases.…”
Section: Resultsmentioning
confidence: 99%